Behavioural Management of Headache Triggers: Three Case Examples Illustrating a New Effective Approach (Learning to Cope with Triggers). Issue 3 (27th July 2015) - Martin, Paul R.; Callan, Moira; Kaur, Archana; Gregg, Karen
<x content-type="archive" xml:space="preserve">Abstract</x> The traditional approach to headache trigger management is to advise avoidance of all triggers, but we have advocated an alternative approach called 'Learning to Cope with Triggers' (LCT), in which the objective is to desensitise headache sufferers to some triggers or to build up tolerance for the triggers, using exposure techniques. A recent publication established the efficacy of this approach to trigger management. Reported here are three cases to illustrate how LCT is used in practice. Two cases were male and one was female, with ages ranging from 32 to 67 years. The headache diagnoses were frequent episodic tension-type headache, migraine without aura, and chronic tension-type headache; all had had headaches since childhood/adolescence. The headache triggers that were the focus of the intervention were heat, tiredness, and stress/anger. Post-treatment, changes in the capacity of the triggers to elicit headaches were reported in all three cases. Reductions in headaches from pre- to post-treatment, and from pre- to 4-month follow-up, were: case 1, 69% and 60% respectively; case 2, 76% and 80% respectively; and case 3, 73% and 61% respectively. Decreases in medication consumption, and enhanced self-efficacy were also recorded.